Hubungan Antara Panjangnya Waktu Kuliah dengan Tanggung Jawab, Kemandirian, dan Kekuatan Ego mahasiswa di Fakultas Kedokteran - Engelberta Pardamean (Medicinus, 2018)
Introduction: Previous studies showed that personality have significant association with the outcome of performance of the students in clerkship. There are three dominance factors of personality such as Ego strength (Es), Responsibility (Re), and Dominance (Do) associated with the length of study of students. This three personality factors will be measured by using MMPI-2 Test. Aim: This study wants to find the mean difference of three factors of personality among the length of study in Faculty of Medicine of University of Pelita Harapan.Methods: This was a cross-sectional study by using the secondary data of MMPI-2 test of student from batch 2005-2006. Personality factors of Ego Strength, Responsibility, and Dominance are measure by mean and standard deviation.Results: Eighty one students were 27 males and 54 female.  From 81 students, 79 persent has finished their medical study within 5.5 years (on time) and 21 persent more than 5.5 years (not on time).Corellation by using spearman test show the significant association of Es with Do (p=0.001 and r=0.357); Es with Re (p=0.001 and r=0.3589). However the Do has no show the significant correlation with Re (p=0.525; r=0.0716). Analysis of t-test show that students who has graduate on time has higher Es (mean=44.12 ± 9.71) than student graduate not on time (mean 42.82 ± 7.97). Score of Do of students has graduate on time (mean 45.85 ± 10)  also higher than late graduate group (mean 41.05 ± 8.45) with p=0.0738. However the Responsibility of graduate on time (mean 48.06 ± 11.21) is lower than late graduated students (mean 49.7 ± 9.66).Conclusion: Ego strength and Dominance has positive association with the length of study.Keywords: ego strength, responsibility, dominance, MMPI-2, medical education